2022
DOI: 10.1371/journal.ppat.1010266
|View full text |Cite
|
Sign up to set email alerts
|

The Coxiella burnetii T4SS effector protein AnkG hijacks the 7SK small nuclear ribonucleoprotein complex for reprogramming host cell transcription

Abstract: Inhibition of host cell apoptosis is crucial for survival and replication of several intracellular bacterial pathogens. To interfere with apoptotic pathways, some pathogens use specialized secretion systems to inject bacterial effector proteins into the host cell cytosol. One of these pathogens is the obligate intracellular bacterium Coxiella burnetii, the etiological agent of the zoonotic disease Q fever. In this study, we analyzed the molecular activity of the anti-apoptotic T4SS effector protein AnkG (CBU07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Future studies will be needed to further elucidate the interaction between CBU1314 and PAF1C and its possible role in modulating host transcription and the immune response. Intriguingly, it was recently shown that the C. burnetii effector AnkG interacts with the host factors DDX21 and 7SK snRNP complex, which are involved in host transcription (Cordsmeier et al, 2022). Thus, C. burnetii may employ multiple effectors that interact with host transcriptional machinery to modulate gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will be needed to further elucidate the interaction between CBU1314 and PAF1C and its possible role in modulating host transcription and the immune response. Intriguingly, it was recently shown that the C. burnetii effector AnkG interacts with the host factors DDX21 and 7SK snRNP complex, which are involved in host transcription (Cordsmeier et al, 2022). Thus, C. burnetii may employ multiple effectors that interact with host transcriptional machinery to modulate gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…While the functions of most effectors are still unknown, some effectors have been found to suppress innate immune responses. C. burnetii has four effectors (AnkG, CaeA, CaeB, IcaA) that suppress cell death pathways (Bisle et al, 2016; Cordsmeier et al, 2022; Cunha et al, 2015; Klingenbeck, Eckart, Berens, & Lührmann, 2013; Lührmann, Nogueira, Carey, & Roy, 2010), three effectors (CBU0885, CBU1676, CBU0388) that modulate the Cell Wall Integrity MAPK pathway in yeast (Lifshitz et al, 2014), and two recently discovered effectors (NopA and CinF) that suppress NF-κB signaling in human cells (Burette et al, 2020; Y. Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The eukaryotic type Ank domain in this protein family might have a role in host-cell attachment and allows the interaction of bacteria with a spectrum of host cell proteins and thus are particularly important in the pathogenic process (Batrukova, Betin, Rubtsov, et al . 2000; Cordsmeier, Rinkel, Jeninga, et al . 2022; Pechstein, Schulze-Luehrmann, Bisle, et al .…”
Section: Discussionmentioning
confidence: 99%
“…AnkG, AnkD and AnkK are ankyrin repeat-containing effector proteins in Cb (Seshadri, Paulsen, Eisen, et al 2003). The eukaryotic type Ank domain in this protein family might have a role in host-cell attachment and allows the interaction of bacteria with a spectrum of host cell proteins and thus are particularly important in the pathogenic process (Batrukova, Betin, Rubtsov, et al 2000;Cordsmeier, Rinkel, Jeninga, et al 2022;Pechstein, Schulze-Luehrmann, Bisle, et al 2020;Voth, Howe, Beare, et al 2009). AnkD has both eukaryotic like domain and F-box domain, but the function is not yet clear (Voth, Howe, Beare, et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the C . burnetii T4SS effector AnkG inhibits host cell apoptosis by interacting with the host proteins p32, importin-α1 and RNA helicase 21 [ 7 , 8 ]. In addition to AnkG, the effectors CaeA and CaeB prevent mitochondrial-dependent (intrinsic) apoptosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%